Negotiating Solidarity and Piety: The Role of Arisan Macul in Reinforcing Communal Cohesion amid Agrarian Change in Java - Diah Ambarumi Munawaroh; Mohammad Isom Yusqi; Eka Sartika (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2025)
This study examines the tradition of Arisan Macul as a form of local wisdom that continues to thrive in the farming community of Torongrejo Village, Batu City, amid rapid social and economic change. The primary focus of this study is to describe how this tradition is carried out, what social, cultural, and religious values are actualized in it, and how these values function as cultural resilience and strengthen the collective identity of the farming community. The research approach is qualitative ethnography, with data collected through participant observation, in-depth interviews, and documentation of 18 purposively selected informants. The results show that Arisan Macul functions not just as a collective mechanism for cultivating land but also as a medium for strengthening social solidarity, togetherness, and knowledge exchange among community members. The socio-cultural values actualized in this practice include mutual cooperation, harmony, tepa selira (mutual respect), and respect for ancestral heritage. On the religious side, Arisan Macul strengthens the practices of praying together, sincerity, gratitude, and the interpretation of hoeing as a form of worship based on Islamic teachings. The integration of these social, cultural, and religious dimensions makes Arisan Macul a form of religious agrarian heritage that functions as a mechanism for cultural resilience for the Torongrejo farming community in the face of modernization and economic change. This study shows that local traditions such as Arisan Macul can be an essential instrument of in cultural preservation, social capital strengthening, and the internalization of Islamic values in contemporary agrarian life.